Reward-related activity in the medial prefrontal cortex is driven by consumption - Horst, Nicole K.; Laubach, Mark (Frontiers in Neuroscience, 2013)
An emerging literature suggests that the mPFC is crucial for the ability to track behavioral outcomes over time and has a critical role in successful foraging. Here, we examine this issue by analyzing changes in neuronal spike activity and local field potentials in the rat mPFC in relation to the consumption of rewarding stimuli. Using multi-electrode recording methods, we simultaneously recorded from ensembles of neurons and field potentials in the mPFC during the performance of an operant delayed alternation task and a variable-interval licking procedure. In both tasks, we found that consummatory behavior (licking) activates many mPFC neurons and is associated with theta-band phase locking by mPFC field potentials. Many neurons that were modulated by the delivery of reward were also modulated when rats emitted bouts of licks during the period of consumption. The majority of these licking-modulated neurons were found in the rostral part of the prelimbic cortex, a region that is heavily interconnected with the gustatory insular cortex and projects to subcortical feeding-related centers. Based on the tight coupling between spike activity, theta-band phase locking, and licking behavior, we suggest that reward-related activity in the mPFC is driven by consummatory behavior.